Implementasi Design Thinking dalam Inovasi Teknologi Pembelajaran Online di Kampus USB YPKP - Aulia Putri, Hasna; Nurpuspita, Delina; Dea Lestari, Fika; Eka Ramdani, Fiki; Anam, Hoerul (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2024)
Online learning is increasingly being implemented in higher education institutions, including Universitas Sangga Buana (USB) YPKP through the Kulon application. However, there are still challenges in using this application, such as difficulties in operating features and an interface that is not user-friendly. This study aims to explore the implementation of design thinking, which focuses on user needs, in developing innovations in the Kulon application as an online learning technology at USB YPKP. The research method used is qualitative, including observation, interviews, and prototype evaluation of the Kulon application involving students, lecturers, and staff as users. Through design thinking stages such as empathy, problem definition, ideation, prototyping, and testing, this research is expected to identify user needs and produce innovative solutions to enhance the quality and effectiveness of online learning at USB YPKP.